Smart Human Security: Economic Safety for Micro, Small and Medium Enterprises (MSMEs) to Face the Impact of the Covid-19 Global Pandemic - Elyta Elyta; Warjio Warjio; Ahmad AzrinBin Adnan (Journal of Government and Civil Society, 2020)
This article aims to develop the concept of human security through economic safeguards for Micro, Small, and Medium Enterprises (MSMEs) in the face of the Covid-19 pandemic. The analysis was carried out using a qualitative approach. This article has found an effort to secure the economy for Micro, Small, and Medium Enterprises (MSMEs) in the face of the Covid-19 pandemic by integrating the hard skills and soft skills approaches. The hard skill approach is an effort made through technical matters, namely primary education in online-based entrepreneurship and training in business management based on Information, Communication, and Technology. Primary education on entrepreneurship and training in the form of technical supervision and management of ICT-based businesses in dealing with the Covid-19 pandemic. The soft skill approach is the provision of understanding and communication skills, especially the ability to conduct diplomacy so that people can have good diplomacy skills and through empathy-buying so that people through empathy can trust again to increase their purchasing power, especially to products from MSMEs. By the author, this method is called smart human security.Artikel ini bertujuan untuk mengembangkan konsep human Secuity melalui pengaman ekonomi terhadap Usaha Mikro Kecil dan Menengah (UMKM) dalam menghadapi pandemi Covid-19. Analisis dilakukan dengan pendekatan kualitatif. Artikel ini telah menemukan upaya pengamanan ekonomi bagi Usaha Mikro Kecil dan Menengah (UMKM)  dalam menghadapi pandemi Covid-19 dengan mengintegrasikan antara pendekatan hard skill dan soft skill. Pendekatan hard skill merupakan upaya yang dilakukan melalui hal-hal teknis yaitu pendidikan dasar dalam berwirausaha berbasis online dan pelatihan pengelolaan usaha berbasis Information, Communication, and Technology. Pendidikan dasar mengenai kewirausahaan dan pelatihan-pelatihan berupa teknis manajemen dan pengelolaan usaha berbasis ICT dalam menghadapi pandemi Covid-19. Pendekatan soft skill merupakan pemberian pemahaman dan kemampuan komunikasi khususnya kemampuan dalam melakukan diplomasi agar masyarakat dapat memiliki keahlian berdiplomasi dengan baik serta melalui empathy-buying agar masyarakat melalui empatinya dapat kembali percaya untuk meningkatkan kembali daya belinya terutama kepada produk dari UMKM. Oleh penulis, cara tersebut disebut sebagai smart human security.